2012
DOI: 10.1021/la203504h
|View full text |Cite
|
Sign up to set email alerts
|

Bioadhesive Control of Plasma Proteins and Blood Cells from Umbilical Cord Blood onto the Interface Grafted with Zwitterionic Polymer Brushes

Abstract: In this work, bioadhesive behavior of plasma proteins and blood cells from umbilical cord blood (UCB) onto zwitterionic poly(sulfobetaine methacrylate) (polySBMA) polymer brushes was studied. The surface coverage of polySBMA brushes on a hydrophobic polystyrene (PS) well plate with surface grafting weights ranging from 0.02 mg/cm(2) to 0.69 mg/cm(2) can be effectively controlled using the ozone pretreatment and thermal-induced radical graft-polymerization. The chemical composition, grafting structure, surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 44 publications
0
45
0
Order By: Relevance
“…In particular, the latter profits from the facile incorporation of reactive groups in special positions, e.g., in the center or at the ends of the polymers, that enable efficient attachment of the macromolecules onto the substrates. Still, classical grafting-from [318][319][320][321][322][323][324][325][326][327][328][329][330][331][332][333][334][335], grafting-to [336][337][338][339][340][341][342][343][344][345][346], and grafting-through [316,347] procedures are of course continuously in use, especially in industrial applications, where the activation of the surfaces for the grafting process by physical means or by simple, "unpretentious" chemistry is preferred for reasons of experience, cost and high-throughput.…”
Section: Synthesis By Chain Growth Polymerizationsmentioning
confidence: 99%
“…In particular, the latter profits from the facile incorporation of reactive groups in special positions, e.g., in the center or at the ends of the polymers, that enable efficient attachment of the macromolecules onto the substrates. Still, classical grafting-from [318][319][320][321][322][323][324][325][326][327][328][329][330][331][332][333][334][335], grafting-to [336][337][338][339][340][341][342][343][344][345][346], and grafting-through [316,347] procedures are of course continuously in use, especially in industrial applications, where the activation of the surfaces for the grafting process by physical means or by simple, "unpretentious" chemistry is preferred for reasons of experience, cost and high-throughput.…”
Section: Synthesis By Chain Growth Polymerizationsmentioning
confidence: 99%
“…The antifouling properties can be affected by packing density, grafting coverage, polymer chain conformation and chemistry [80]. For example, protein fouling resistance increased with increasing polymer chain length and grafting coverage [59,81]. …”
Section: Membrane Surface Modification Using Hydrophilic Materialsmentioning
confidence: 99%
“…The use of polymers containing zwitterionic groups such as phosphatidylcholines and sulfobetaines, 5-10 which originate from the simulation of biomembranes, 9,11 has been proposed to modify the surface of biomaterials. [12][13][14] A significant reduction in protein adsorption has been demonstrated 5,[8][9][10][12][13][14][15][16][17][18] and attributed to the formation of a hydration layer on the material surface [5][6][7][9][10][11][12][13][14]16,17,19 that prevents the conformational alteration of these proteins. 9,11,13,14,19 Previous researchers 7,13,16,20,21 reported that sulfobetaine application on substrate surfaces reduced bacterial adhesion.…”
Section: Introductionmentioning
confidence: 99%